KEINDAHAN SEBAGAI ELEMEN SPIRITUAL PERSPEKTIF ISLAM TRADISIONAL - Andi Herawati (Universitas Gadjah Mada, 2015)
Beauty for most part eventually seen as the science of form, more than that is of the essential part of human living and the way we look at it by the time become more discern as it invites the philosophical vibration. It becomes a consiousness through the questions about the creation of the cosmos and meditation upon the Almighty. Whether aware or not, human need beauty through out their living, at the same time is a spiritual journey. Beauty in Traditional Islam is also able to ascending human, create the the awareness of plurality, and at the last it aso to born out the sense of the Sacred manifested thorugh the form of art, culture, calligraphy, and the whole cosmos. At last, beauty has its role in spiritual journey through self emptiness, from the false self to the true self.